Toefl Result of Politeknik Harapan Bersama Tegal Student’s Majoring Mechanical Engineering - Romadhon, Syaefani Arif; Yuvita, Yuvita (Jurnal Bahasa Inggris, 2018)
This research was done to see students’ TOEFL score especially for fifth semester of Politeknik Harapan Bersama Tegal majoring Mechanical Engineering. Descriptive design using quantitative approach was chosen by the researcher. The sample is 45 students of Mechanical Engineering Study Program. The TOEFL test was used as research instrument. Descriptive statistics was used as data analysis technique, mean and percentage. The result of this research showed that student obtained problems in getting a TOEFL score with an average score 424 which was still at the basic proficiency category. The researcher found that the highest problem received by the students is listening section where student obtained correct answers only 23.7%. The students obtained the lowest score is in the short conversation with the percentage 31.27%. Then the structure and written expression, students obtained average score lowest in structure with a percentage 30.6%.